"Popularization" of archaeology in the Argentinian newspapers: social representation and education - (:unkn) unknown (asbl Kinéon, 2009)
This paper examines how archaeology is represented in scientific articles of Argentinean newspapers of national circulation published between 1994 and 2006. The aim of this project is to learn about the social construction of archaeological knowledge in these spaces. In these articles, the archaeological information is reorganized and recontextualizated: archaeological concepts are set in relation to other concepts that are not from the archaeological field. In this way other narratives about the past can be made. The newspapers analyzed here, tend to cluster the archaeological articles into groups according to their geographical location or by subject matters of interest to the public. As informal educators, in Argentine, mass media has played a prominent role in the popularization of science and was one of the most used devices for this purpose. For that reason, they can be seen as a space that allows us to analyze those uses and the social needs concerning archaeology. This information is needed, although it is not enough, to create communication strategies focused on the public and to stimulate the local use of that knowledge.

Cet article examine comment l’archéologie est représentée dans les articles scientifiques des quotidiens nationaux (Argentine) publiés entre 1994 et 2006. Le but de ce projet est de découvrir la construction sociale de la connaissance archéologique dans ces espaces. Dans ces articles de presse, l’information archéologique est réorganisée et recontextualisée : les concepts archéologiques sont mis en relation avec des concepts d’autres disciplines. De cette manière, il est possible de reconstituer le passé. Les quotidiens analysés dans ce cas, tendent à rassembler les articles archéologiques dans des groupes selon leur appartenance géographique ou par sujet. En tant qu’éducateurs informelle, en Argentine, les médias de masse ont joué un rôle important dans la popularisation de la science et furent un des principaux outils pour la difusion. Pour cette raison, ils peuvent être vus comme un espace qui nous permet d’analyser cet usage et les besoins sociaux concernant l’archéologie. Cette information est nécessaire, bien qu’elle ne doit pas être unique, pour créer des stratégies tournées vers le public et pour stimuler l’utilisation locale de cette connaissance.
Keywords: Arqueología